Post Orthodontic Cosmetic Detailing - Snigdha Pattanaik (Indian Journal of Forensic Medicine & Toxicology, 2020)
Post orthodontic cosmetic detailing is perhaps one of the most deceiving and difficult phases of orthodontictreatment. The cosmetic detailing procedures are considered as a part of the total scheme of treatmentto enhance the stability and esthetics of the cases. In recent times, a great deal of emphasis is placed onachieving perfect finishing and detailing of the orthodontic treatment, so that the results are pleasing to theeye. This article aims to provide comprehensive knowledge about post orthodontic cosmetic detailing.